Repeated unrewarded scent exposure influences the food choice of stingless bee foragers, Melipona scutellaris - Roselino, Ana Carolina [UNESP]; Hrncir, Michael (Academic Press Ltd Elsevier B.V. Ltd, 2012)
The social organization of foraging processes is a principal key to the ecological success of eusocial insects. Floral odours brought back to the colony by successful foragers are important sources of information underlying an individual's decision about which resource to collect. Food-source-naive individuals memorize and use this olfactory information when searching for food in the field. Odour familiarization as mechanism underlying the coordination of foraging processes has received little attention so far. Here, we asked whether and to what extent foraging decisions of stingless bees, Melipona scutellaris, are influenced by preceding unrewarded olfactory experiences. In a classical conditioning assay (proboscis extension reflex, PER, assay), foragers were exposed to a scented airflow, during which they either received (experimental group CS+) or did not receive (experimental group CS-) a sugar solution as reward. Subsequently, bees of both experimental groups were introduced into an arena where they could choose between two scented feeders, one of which carried the odour used during the PER assay. Independently of whether foragers had received a sucrose reward during scent exposure, between 70% and 75% of the individuals chose the food source that carried the conditioned odour in the choice arena. Bees from the control groups (harnessed or not; no scent exposure), by contrast, showed no preference for either of the two feeders. These findings point to the importance of preceding olfactory experiences for the food choice of M. scutellaris and suggest that both associative learning during trophallaxis as well as familiarization may influence to a similar extent the foraging decisions of these bees in natural settings. Crown Copyright (C) 2011. Published on behalf of The Association for the Study of Animal Behaviour by Elsevier Ltd. All rights reserved.
Keywords: familiarization; floral odour; foraging decision; Melipona scutellaris; PER assay; scent learning; stingless bee